Modification of zinc-doped polydopamine coating on pure titanium surface and its corrosion resistance: A preliminary study - MEI Yukun, ZHANG Jianlan, QIU Jing (Editorial Office of Stomatology, 2024)
Objective To prepare zinc-loaded polydopamine coating on the surface of pure titaniumand investigate its biocompatibility and corrosion resistance. Methods Pure titanium specimens were successively immersed in a dopamine alkaline solution and a zinc sulfate solution to form a zinc-loaded polydopamine coating on the surface of the specimens. The smooth titanium surface and the polydopamine-coatedtitanium surface were used as the control group, and the zinc-containing polydopamine-coated titanium surface was used as the experimental group. Scanning electron microscopy(SEM) was used to observe the micro-morphology of the specimen surface, and energy dispersive spectrometer(EDS) was used to determine the binding of zinc elements on the polydopamine coating. The hydrophilicity of the specimen surface was detected by a contact angle meter. L-929 fibroblasts were cultured in vitro and the biocompatibility of the modified titanium surface was evaluated by CCK-8 assay. An electrochemical potentiostat was used to obtain the open-circuit potential and potentiodynamic polarization curves of specimens of each group in artificial saliva to analyze the effect of zinc-doped polydopamine coating on the corrosion resistance of titanium surface. Results SEM and EDS analyses showed that there were differences in the surface micro-morphology among three groups, and the presence of zinccould be detected on the surface of the specimens in the zinc-doped polydopamine coating group. The hydrophilicity of the specimen surface was enhanced after coating modification.The results of in vitro experiment revealed that the zinc-doped polydopamine coating had good biocompatibility.The open-circuit potential and potentiodynamic polarization curves obtained from electrochemical tests and their fitting data showed that the zinc-doped polydopamine coating group had the strongest corrosion resistance, followed by the polydopamine coating group, and the smooth titanium group had the smallest. Conclusion Zinc-doped polydopamine coatingscanbe successfully prepared on titanium surfaces usingchemical immersion method, and the modified titanium surfacespossess good biocompatibility and corrosion resistance.